Effect of physical activity on peak expiratory flow and the 6-minute walk test - Jakubowska, Klaudia; Pawelec-Winiarz, Magdalena; Włosiński, Michał; Cichosz, Michał (Journal of Education, Health and Sport, 2022)
The study conducted research aimed at assessing the influence of physical activity on peak expiratory flow (PEF) and the 6-minute walk test (6MTW). The research was carried out at the Department of Systemic Rehabilitation - Post Covid at the Pj-Med Rehabilitation Hospital in Popielówek from June 2021 to April 2022. The inclusion criteria for the studies was a positive PCR test performed up to one year after the end of treatment. Exclusion criteria - active inflammation (CRP <5 or increasing CRP level), acute pulmonary embolism, heart failure with impaired left ventricular ejection fraction (LVEF <35%) without cardioverter-defibrillator protection, unstable disease outside the circulatory system, unstable coronary artery disease, uncontrolled arrhythmias. The entire rehabilitation program lasted 6 weeks. The beginning of rehabilitation services was on average 4 months after the positive PCR result (min. 1 month and max. 11 months). A statistically significant difference was observed in the PEF parameter and in the 6MTW test before and after rehabilitation.